2018
DOI: 10.1188/18.cjon.e64-e70
|View full text |Cite
|
Sign up to set email alerts
|

HPV Literacy: The Role of English Proficiency in Korean American Immigrant Women

Abstract: HPV literacy of Korean American immigrant women was moderate, and knowledge about HPV detection items was particularly low. Age was the only predisposing factor that had a significantly negative association with HPV literacy, whereas education level and English proficiency had a significant positive relationship with HPV literacy. Health status as a need factor was significantly positively associated with HPV literacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 20 publications
2
18
2
Order By: Relevance
“…Our data demonstrate that education level remained independently associated with knowledge after adjustment for all factors in our model. This finding aligns with studies in other domains of reproductive health that indicate health literacy correlates with increased education level [ 32 – 34 ]. In our study, however, after analyzing LR and HR groups separately, education was no longer a significant factor associated with fertility knowledge in each group, suggesting that identifying those with attainment of formal academic education was insufficient.…”
Section: Discussionsupporting
confidence: 90%
“…Our data demonstrate that education level remained independently associated with knowledge after adjustment for all factors in our model. This finding aligns with studies in other domains of reproductive health that indicate health literacy correlates with increased education level [ 32 – 34 ]. In our study, however, after analyzing LR and HR groups separately, education was no longer a significant factor associated with fertility knowledge in each group, suggesting that identifying those with attainment of formal academic education was insufficient.…”
Section: Discussionsupporting
confidence: 90%
“…Concerning HPV vaccine awareness, the current study found that high English proficiency was significantly associated with all four racial/ethnic groups. Although previous studies investigating the association between LEP and the HPV vaccine awareness were not found, Lee et al, (2018) determined the relationship between HPV literacy and LEP and indicated that those with high levels of English proficiency had higher HPV literacy levels than those with a low level of English proficiency among Korean women. While the relationship between LEP and the HPV vaccine among Hispanics was not addressed in the previous study, LEP as a barrier to adequate health communication within this population has been documented in previous studies (Riera et al, 2015;Sarkar et al, 2016).…”
Section: Discussionmentioning
confidence: 89%
“…Each racial/ethnic group demonstrated barriers regarding awareness of HPV and the HPV vaccine. With language barriers posing a risk to taking preventive health actions, HPV interventions can be improved by using tailoring materials to individuals' native languages, particularly for Hispanic and Asian Americans, as existing literature indicates that they frequently experience greater disadvantages regarding English proficiency and have greater difficulty finding health care providers who speak their native languages (Jenny et al, 2013;Reimer et al, 2014;Lechuga et al, 2016;Lee et al, 2018). In addition to developing targeted materials, implementing the presence of an interpreter during interventions and healthcare appointments, particularly in settings with larger populations of non-English speaking individuals, has great potential to address patients' needs and concerns and aid them in gathering the necessary information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17,23 Some have considered education as an enabling factor because of its relationship with English proficiency and social economic status, both of which facilitate the acquisition of health literacy. 9,20,24 However, it is more commonly considered as a predisposing factor because it does not fluctuate and pertains to the fixed social status that a person has already obtained. The enabling factors examined in the present study included whether the individual had private health insurance coverage, a designated place for medical care, a doctor in charge, and the frequency of doctor visits.…”
Section: Conceptual Frameworkmentioning
confidence: 99%